In-Silico Analysis of Eugenol and Beta-Caryophyllene Compounds in Clove (Syzygium aromaticum L.) on NF-kB Protein As Anti-inflammatory Agent In Atherosclerosis - Astuti Kusumorini; Yani Suryani; Fauziah Qurota Ayuni; Opik Taupiqurrohman (Elkawnie, 2024)
Abstract: Atherosclerosis is one of the leading causes of cardiovascular disease, which is ranked as the world's deadliest disease by WHO. The NF-kB protein is important in the development of atherosclerosis. Inhibiting the inflammatory response pathway via the NF-kB protein can inhibit the development of atherosclerosis. Clove (Syzygium aromaticum L.)  is one of the plants with anti-inflammatory and anti-atherosclerotic properties. The main constituents of clove are eugenol and beta-caryophyllene (BCP), which have been extensively researched for their anti-inflammatory properties. This study aims to simulate the potency of eugenol and BCP compounds by measuring their binding affinity and observing the interactions that occur when they are tethered to the active site of the NF-kB protein. The research was carried out in silico method, using molecular docking techniques. According to the analysis, eugenol and BCP had binding affinity values of -5.9 kcal/mol and -7.0 kcal/mol, respectively. The eugenol compound forms 12 interactions on the active site of NF-kB protein, consisting of the hydrogen bond, carbon-hydrogen bond, pi-sigma, alkyl, and Van Der Waals interactions. Meanwhile, 5 interactions form between BCP and NF-kB protein, including Van Der Waals, alkyl, and pi-sigma interactions. The bond affinity calculations of the eugenol-NF-kB protein are stronger than the BCP-NF-kB protein. In addition, the number of interactions formed by eugenol- NF-kB protein is greater than BCP-NF-kB protein. Based on the description, the eugenol compound has better potential to influence the function of the NF-kB protein than BCP, so the eugenol compound is recommended for in vitro and in vivo anti-inflammatory tests.Abstrak: Aterosklerosis adalah salah satu penyebab utama penyakit kardiovaskular, yang menduduki peringkat penyakit paling mematikan di dunia menurut WHO. Protein NF-kB penting dalam perkembangan aterosklerosis. Menghambat jalur respon inflamasi melalui protein NF-kB dapat menghambat perkembangan aterosklerosis. Cengkih (Syzygium aromatikum L.) merupakan salah satu tanaman yang mempunyai sifat anti inflamasi dan anti aterosklerotik. Kandungan utama cengkeh adalah eugenol dan beta-caryophyllene (BCP), telah banyak diteliti sifat anti inflamasinya.  Penelitian ini bertujuan untuk mensimulasikan potensi senyawa eugenol dan BCP dengan mengukur afinitas pengikatannya dan mengamati interaksi yang terjadi ketika ditambatkan pada sisi aktif protein NF-kB. Penelitian dilakukan secara in silico dengan menggunakan teknik molekuler docking. Berdasarkan analisis, eugenol dan BCP memiliki nilai afinitas pengikatan masing-masing sebesar -5,9 kkal/mol dan -7,0 kkal/mol. Senyawa eugenol membentuk 12 interaksi pada sisi aktif protein NF-kB, terdiri dari interaksi ikatan hidrogen, ikatan karbon-hidrogen, pi-sigma, alkil, dan Van Der Waals. Sementara itu, terjadi 5 interaksi antara protein BCP dan NF-kB, antara lain interaksi Van Der Waals, alkil, dan pi-sigma. Perhitungan afinitas ikatan protein eugenol-NF-kB lebih kuat dibandingkan protein BCP-NF-kB. Selain itu, jumlah interaksi yang terbentuk protein eugenol-NF-kB lebih besar dibandingkan protein BCP-NF-kB. Berdasarkan uraian tersebut, senyawa eugenol mempunyai potensi yang lebih baik dalam mempengaruhi fungsi protein NF-kB dibandingkan BCP, sehingga senyawa eugenol direkomendasikan untuk uji antiinflamasi dengan metode in vitro dan in vivo.